Solidarity Towards the Poor Based on the Ideas of Pope Francis - Bonaventura Dwi Putra; Yohanes Wahyu Rusmana (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Solidarity is a value rooted in the understanding and commitment of faith to respond to and seek solutions to the concrete problems of human life for the development of life together. Solidarity is also one of the values and life practices of the Church that has been internalized and passed down by Jesus and his disciples. However, over time, the value of solidarity has become increasingly eroded by the currents of the times. In the situation of the weakening of human solidarity values in the post-modern era, Pope Francis, in his pastoral vision, calls on the faithful to internalize and cultivate the value of solidarity, especially towards the small, the poor, the oppressed, and the forgotten.Through this article, the author focuses on exploring Pope Francis's ideas about solidarity towards the poor. The research method used is qualitative literature study with a descriptive analysis approach. The purpose of compiling this article is to explore and discover the meaning of solidarity based on Pope Francis's ideas. The results of the research show that reflections and ideas about solidarity from Pope Francis can contribute to theological reflection and can also become priority values that can be lived and interpreted within the framework of means of accountability of faith and salvation in the midst of communal life.